Effect of Gaguk fish (Arius thalassinus) cookies on macronutrient and micronutrient intake in anemic adolescent girls - Rian Triyunita; Masrul Masrul; Endrinaldi Endrinaldi (AcTion: Aceh Nutrition Journal, 2025)
Adolescence is a transition period from childhood to adulthood that requires nutritional intake of iron. Children with iron deficiency are highly susceptible to anemia. This study aimed to determine the effect of rainbow gaguk fish (Arius thalassinus) cookies on macro-and micronutrient intake in adolescent girls with anemia. This study used preliminary data from the Bengkulu Provincial Health Office, where many students experienced anemia in one junior high school. In the selection of samples using simple random sampling, 50 g of rainbow gaguk fish biscuits were used. The dependent variable in this study was gaguk fish. The independent variables were the macro-and micronutrient intake. This study employed a quasi-experimental pre-post-test intervention research using a purposive sampling design. Data analysis was performed using the paired t-test and Wilcoxon test at 95% confidence interval (CI). The results showed that before giving fish cookies, energy intake was 44,4%, protein 51,5%, carbohydrate 51,4%, vitamin B12 52,5%, folate 38,5%, iron 54%, and zinc 45,6%; after an increase in energy intake, energy intake was 55,8%, protein 62,3%, carbohydrate 52,1%, vitamin B12 65%, folate 39,1%, iron 74%, and zinc 81,1% (p<0,001). In conclusion, the provision of rainbow biscuits to adolescent girls with anemia improved significantly.